Antimicrobial resistance and natural alternatives: in vitro efficacy of Hungarian propolis against feline and bovine Tritrichomonas foetus - Kerek, Ádám; Yurt, Attila; Szabó, Ábel; Tuska-Szalay, Barbara; Jerzsele, Ákos (Frontiers in Veterinary Science, 2025)
IntroductionAntimicrobial resistance (AMR) is a critical One Health challenge affecting both human and animal health. Tritrichomonas foetus, a protozoan parasite causing reproductive and gastrointestinal disorders in cattle and cats, presents a growing threat due to limited treatment options. While nitroimidazoles such as ronidazole remain the standard of care, their use is restricted in food-producing animals and associated with emerging resistance in feline strains. Propolis, a complex natural resin produced by bees, has demonstrated antimicrobial and antiparasitic activity in other protozoan infections.MethodsThis in vitro study assessed the minimum lethal concentrations (MLC) of ethanolic propolis tincture from the Észak-Alföld region of Hungary against feline- and bovine-derived T. foetus strains, compared to four nitroimidazoles.ResultsPropolis showed promising activity, with an MLC of 1.25 mg/ mL for feline isolates and 0.16 mg/mL for bovine isolates after 48 h. Ronidazole demonstrated reduced efficacy against feline isolates (MLC 32 μg/mL), suggesting partial resistance, whereas bovine isolates remained susceptible (MLC 1 μg/mL).DiscussionOur findings highlight propolis as a potential alternative treatment for T. foetus, particularly in cattle where nitroimidazole use is prohibited. Standardizing propolis tincture and conducting in vivo studies will be essential to translate these results into clinical applications. This study contributes to efforts to combat AMR and develop sustainable, natural therapeutic alternatives in veterinary medicine, aligning with One Health principles.